THE EMPLOYABILITY WHOLE WELDED STRUCTURES OF RAILWAY BRIDGES - V. I. Kyrian (Nauka ta progres transportu, 2008)
In the work the operating experience and methods of increasing the reliability and durability of steel bridges are investigated.